Implementasi Modul Ajar Di Sekolah - Yulia Wulandari,; Novan Yakhin Gamaliel,; Nanda,; Matius Timan Herdi Ginting , (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The learning process was based on the "I Am Special as God's Creation" Teaching Module in Christian Religious Education for first grade elementary school students. This learning activity aims to help students understand that they are God's precious and unique creations. Furthermore, it encourages students to demonstrate mutual respect, speak politely, and accept differences in their daily school lives. Through this activity, teachers were able to assess the effectiveness of the teaching module, the methods used, and student responses during the lesson. The implementation of the "I Am Special as God's Creation" Lesson Plan/Teaching Module went well and met most of the learning objectives. Students demonstrated an increased understanding of their worth as God's creations and were able to express positive things about themselves. Mutual respect, the use of polite language, and self-confidence began to emerge in interactions during the lesson. The creative activity of tracing a palm with a symbol of a personal character significantly helped students express their uniqueness. Despite some constraints related to time and assistance with students who needed additional support, the learning process proceeded smoothly and meaningfully. By improving media and time management, it is hoped that implementation at the next meeting will be more effective and provide a deeper learning experience for students.